Continuous Quasi Gyrolinear Functionals on Möbius Gyrovector Spaces. (18th June 2020) - Watanabe, Keiichi
Abstract : We investigate a class of functionals on Möbius gyrovector spaces, which consists of a counterpart to bounded linear functionals on Hilbert spaces.